Presentation of singularia and pluralia tantum nouns in a course of Russian as a foreign language - Nagaitseva, N. I.; Romanov, Yu. (Гельветика, 2020)
This article considers singularia and pluralia tantum nouns; despite the absence of this topic in programs on teaching Russian as a foreign language (RFL), it must be acknowledged that singularia tantum nouns constitute a significant layer of vocabulary and are quite commonly used, and pluralia tantum nouns are closely linked to cultural discourse and cannot be painlessly excluded from lexical system of the Russian language. Although this phenomenon has been thoroughly studied in classical editions of Russian grammar, problems of category of number and in particular singularia and pluralia tantum nouns are still widely discussed by modern linguists (as is noted, complex subjects can be designated both as forms of singular and forms of plural, therefore the three groups of nouns can be found: pluralia tantum (a single object indicated by plural: ворота), a full-numbered paradigm (one object is indicated by singular: ракушка), and nouns with a paradigm fluctuation (one object is indicated by both singular and plural: дверь / двери); there is a dramatic rise in the use of plural forms of many abstract nouns (риск, продажа) forming a crucial change in the development trend of Russian abstract noun number paradigms). We assume that in RFL teaching, it is important to follow the principles of step by step presentation of theoretical information on this topic (common singularia and pluralia tantum nouns, their grammatical properties, derivative characteristics; proper singularia and pluralia tantum nouns; synonymy, antonymy, and homonymy of singularia and pluralia tantum nouns; occasionalisms, etc.) to help students reach a higher level of Russian language proficiency.

У статті розглянуто іменники singularia та pluralia tantum. Не зважаючи на відсутність цієї теми у програмах викладання російської мови як іноземної (далі – РЯІ), треба визнати, що іменники singularia tantum становлять значний прошарок лексики та є доволі вживаними, а іменники pluralia tantum тісно пов’язані з культурологічним дискурсом і не можуть бути безболісно виключені з лексичної системи російської мови. Хоча цей феномен досить ретельно вивчався в класичних виданнях російської граматики, проблеми категорії числа та іменників singularia tantum та pluralia tantum зокрема продовжують широко обговорюватися сучасними лінгвістами. Наприклад, ідеться про те, що складні речі позначають як формами однини, так і формами множини, тому вирізняють три групи іменників: pluralia tantum (окремий предмет, позначений множиною: ворота); ті, що мають повну парадигму (один об’єкт позначається одниною: ракушка), та іменники з коливанням парадигми (один об’єкт позначається як одниною, так і множиною: дверь/двери). Зазначають, що відбувається різке зростання використання множинних форм багатьох абстрактних іменників (риск, продажа), що надзвичайно змінює тенденції розвитку парадигм числа абстрактних іменників у російській мові). Ми виходимо з того, що у викладанні РЯІ важливо дотримуватися принципів покрокової презентації теоретичної інформації за темою: загальні іменники singularia та pluralia tantum, їхні граматичні властивості, дериваційні характеристики; власні іменники singularia та pluralia tantum; синонімія, антонімія й омонімія іменників singularia та pluralia tantum; оказіоналізми тощо», що допомагає студентам підвищити рівень володіння російською мовою.
Презентація іменників singularia та pluralia tantum у курсі російської мови як іноземної
Keywords: singularia tantum; pluralia tantum; category of number; Russian as a foreign language; L2 learning; категорія чисел; викладання другої мови; російська граматика; лінгвістика